2005
DOI: 10.2527/2005.83113x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of single nucleotide polymorphisms in genes residing on chromosomes 14 and 29 for association with carcass composition traits in Bos indicus cattle1,2

Abstract: Objective of this study was to assess the association of SNP in the diacylglycerol O-acyltransferase 1 (DGAT1), thyroglobulin (TG), and micromolar calcium-activated neutral protease (CAPN1) genes with carcass composition and meat quality traits in Bos indicus cattle. A population of Brahman calves (n = 479) was developed in central Florida from 1996 to 2000. Traits analyzed were ADG, hip height, slaughter weight, fat thickness, HCW, marbling score, LM area, estimated KPH fat, yield grade, retail yield, sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
4
28

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 15 publications
13
138
4
28
Order By: Relevance
“…Higher GG frequency was prevalent in all but one group, the Rubia Gallega x Nelore, in which the AG genotype was most prominent. In contrast with the results presented by Casas et al (2005), which showed absence of the A allele in a B. indicus population of the Brahman breed, this study revealed a 21.9% frequency in Nelore B. indicus. Thus, for the fi rst time, it was possible to study the association between this polymorphism and traits of economical interest in B. indicus bovines.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Higher GG frequency was prevalent in all but one group, the Rubia Gallega x Nelore, in which the AG genotype was most prominent. In contrast with the results presented by Casas et al (2005), which showed absence of the A allele in a B. indicus population of the Brahman breed, this study revealed a 21.9% frequency in Nelore B. indicus. Thus, for the fi rst time, it was possible to study the association between this polymorphism and traits of economical interest in B. indicus bovines.…”
Section: Resultscontrasting
confidence: 99%
“…According to Casas et al (2005), polymorphisms that segregate and associate with traits of interest in B. taurus may or may not segregate in B. indicus. Thus, it is necessary to develop and use other markers in candidate genes or chromosomal regions, to allow association studies in B. indicus.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reasons may be because yak and cattle belong to Poephagus and Bos, respectively, owing to the differences in genome between two bovine species, the gene regulation mode may change. Casas et al (2005) have demonstrated that the allele frequencies of some molecular marker locus in chromosomes 14 and 29 associated with carcass traits are different between the domestic cattle (Bos taurus) and zebu cattle (Bos indicus). SNPs in the TG gene were significantly associated with the marble scores in domestic cattle, but no association in zebu castles, suggesting that new suitable molecular markers need to be found in zebu populations.…”
Section: Discussionmentioning
confidence: 99%
“…The data for Study 6 was first analysed in [4]. The excluded studies were described in [22] and [5]. All other studies were unpublished technical reports provided by Genetic Solutions Pty.…”
Section: Dataset For Meta-analysismentioning
confidence: 99%
“…Casas et al [5] investigated the association between the TG5 marker and USDA marble score in a sample of 467 Brahman (Bos indicus) cattle. They found no association, but the sample included only 18 CT and 7 TT animals.…”
Section: Other Studiesmentioning
confidence: 99%